2016
DOI: 10.1002/2327-6924.12402
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes toward evidence‐based clinical decision support tools to reduce exposure to ionizing radiation

Abstract: Background and purpose A large degree of variation in clinical practice exists among clinicians evaluating and treating individuals with minor head injuries. Noncontrast head computerized tomography (CT) scans are commonly used to assess for intracranial damage in patients presenting with head injury. This practice is not supported by the evidence and poses harm to patients by increasing exposure to ionizing radiation. This form of radiation exposure increases the risk of developing cancers over the course of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
(21 reference statements)
0
8
0
Order By: Relevance
“…Conversely, several tools exist to address medical radiation exposure, including physician education, calculators, etc. 33 Lukoff and Olmos 34 reported that documenting radiation doses as a “vital sign” on electronic medical records can increase visibility and help calculate radiation doses before ordering an imaging test. Also, Yu et al 35 described mitigating radiation exposure by optimizing the technical aspects of CT while steadfastly justifying its clinical need.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, several tools exist to address medical radiation exposure, including physician education, calculators, etc. 33 Lukoff and Olmos 34 reported that documenting radiation doses as a “vital sign” on electronic medical records can increase visibility and help calculate radiation doses before ordering an imaging test. Also, Yu et al 35 described mitigating radiation exposure by optimizing the technical aspects of CT while steadfastly justifying its clinical need.…”
Section: Discussionmentioning
confidence: 99%
“…Tan et al (2018), who completed a study to evaluate compliance with the CCHR, report that the CCHR has an awareness rate of 31% and a usage rate of 12% in the United States. Other reported factors include local standards of practice, perceived patient expectations, and administrative pressure for higher reimbursement (Tung et al, 2018; Zakhari & Sterrett, 2016).…”
Section: Available Knowledgementioning
confidence: 99%
“…Multiple studies also support the use of education to increase awareness and, in turn, increase the use of the CCHR. Zakhari and Sterrett (2016) report an increase in use of the CCHR after the implementation of an intervention to educate providers on its use. Similarly, it was reported that providers were more likely to adopt the tool if it was being successfully used by their colleagues.…”
Section: Available Knowledgementioning
confidence: 99%
“…16 Studies focused on attitudes and adherence showed that common reasons physicians ordered a head CT scan were to confirm or exclude a diagnosis, fear of missing a diagnosis, and to expedite a diagnosis. 17 Zakhari and Sterrett 18 indicated that clinicians would adopt the CCHR to a moderate extent if they found it appealing and it was required by a governing authority. The greatest barrier to applying the CCHR was the clinician's fear of missing a diagnosis.…”
Section: Literature Reviewmentioning
confidence: 99%